Influence of Forest Conditions on the Spread of Scots Pine Blister Rust and Red Ring Rot in the Priangarye Pine Stands - Andrey I. Tatarintsev; Pavel I. Aminev; Pavel V. Mikhaylov; Andrey A. Goroshko (Land, 2021)
Scots pine blister rust and red ring rot are common on Scots pine throughout its entire range. Specialists do not explain a significant variation in the prevalence of the diseases uniquely since it depends on complex ecological and silvicultural factors. The aim of this research is to study the influence of forest growth conditions on the incidence of Scots pine blister rust and red ring rot in pine stands of the Priangarye (territory located along the lower reaches of the Angara within the Krasnoyarsk Krai). The research methods included a detailed forest pathological examination of prevailing pine forest types, specific symptom-based macroscopic diagnosis of the diseases, data analysis using parametric and non-parametric statistical tests. Forest growth conditions indicators included type of forest, habitat conditions, and bonitet class of forest stands. The incidence of Scots pine blister rust and red ring rot in pine forests of the Priangarye reaches the extent of moderate and severe damage, respectively. The prevalence of Scots pine blister rust is significantly higher in low-bonitet lichen pine forests; the incidence rate increases along the gradient of decreasing fertility and soil moisture level. The incidence of red ring rot is significantly higher in herb-rich pine forests, in gradations of maximum soil fertility and medium soil moisture. The revealed patterns are explained by the bioecological characteristic features of pathogens (for red ring rot—additionally by factors of structural immunity in pine trees). The results of the research should be recognized in the organization of forestry practice.